Pengaruh Segmentasi Pasar, Produk dan Price terhadap Keputusan Nasabah Menggunakan Jasa PT. Pegadaian Syariah Cabang Kuala Simpang - Putri Rahmayani; Dewi Shinta W. Lubis (CIVITAS: Jurnal Studi Manajemen, 2022)
PT. Pegadaian (Persero) is one of the non-banking credit institutions that serve the public in order to get funds quickly through credit. To improve customer decisions PT. Pegadaian is highly demanded for all branch outlets to increase market segmentation. This study aims to analyze the effect of Market, Product and Price Segmentation on Customer Decisions through customer trust in PT. Pegadaian Syariah Kuala Simpang Branch. This study uses a quantitative method involving 133 respondents, sampling using Random Sampling is a sample determinant that provides equal opportunities for each population customer to be sampled. Data collection is done by using questionnaires. The data obtained were analyzed using statistical formulas, with multiple linear regression model, namely path analysis which was processed with SPSS version 18 program. The results of the study showed that partially the quality of service and product had a positive effect on PT. Pegadaian Syariah Kuala Simpang Branch.